2016
DOI: 10.1177/0142723716640187
|View full text |Cite
|
Sign up to set email alerts
|

Negative sentences in children with specific language impairment

Abstract: This study used elicited production methodology to investigate the negative sentences that are produced by English-speaking children with specific language impairment (SLI). Negative sentences were elicited in contexts in which adults use the negative auxiliary verb doesn't (e.g., It doesn't fit). This form was targeted to see how negative markers (not, n't) interact with the 3rd person singular -s in the grammars of children with SLI. A robust sample of negative sentences was collected from 63 children: 21 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…As English children with DLD produced ungrammatical/ non-adult negative structures in the experiments in Thornton et al (2016), the DLD group in the present study produced ungrammatical sentences in Structure A, like those in (12), typical Chinese ungrammatical negative sentences. These findings were consistent with those in Tsai (2011) and indicated that children with DLD are not sure about the usage of negative markers in negating sentences with the aspectual marker-le.…”
Section: Dld Group's Difficulty With Structure Asupporting
confidence: 55%
See 3 more Smart Citations
“…As English children with DLD produced ungrammatical/ non-adult negative structures in the experiments in Thornton et al (2016), the DLD group in the present study produced ungrammatical sentences in Structure A, like those in (12), typical Chinese ungrammatical negative sentences. These findings were consistent with those in Tsai (2011) and indicated that children with DLD are not sure about the usage of negative markers in negating sentences with the aspectual marker-le.…”
Section: Dld Group's Difficulty With Structure Asupporting
confidence: 55%
“…An elicited production task ( Thornton et al, 2016 ; Schaeffer, 2018 ) was used to investigate the production of Structure A (NP- mei -VP). The participants were required to describe the actions indicated by the experimental materials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…the boy/s walked), whereas 3S marks both tense and subject–verb agreement (e.g. he walks vs. they walk), indicating that 3S is a more complex morphosyntactic structure for children to master (Thornton et al, 2016). At A2, the GET (90 probes) was re-administered.…”
Section: Methodsmentioning
confidence: 99%